A retórica do sobrenatural na TV: um estudo da persuasão no neopentecostalismo - Mellet, Luiz Ernesto (2008)
In the past few years, the neopentecostal movement has gain space on the brasilian religious field. The progress is based, among any others reasons, in the soft way to accept certain conducts and the sectary strictness that prevail in the others religious communities that follows the christianism in the country. The Igreja Mundial do Poder de Deus was created in the end of the last century and since then has been embracing in its temples a crescent number of followers. The systemic use of television in the propagation of its creed encored in the cure and solving problems of the world, responds, in part, for the success of this agremiation. What its appearance adds to the national neopentecostalismo,the influence of persuasion and efficiency of electronic media in the adhesion of followers are the reflexes that guided this dissertation.